Development of Virtual Reality Web-Based Learning in Teaching English Language Skills (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2025)
The transformation of learning media is happening rapidly, requiring responsive adaptation from both learners and educators. Virtual Reality (VR)-based media has gained significant popularity among students, offering innovative and immersive learning experiences. In contemporary education, providing adequate opportunities for learners to engage deeply with the material is essential, especially in acquiring English, which is often considered challenging through traditional methodologies. This study aims to develop Virtual Reality-based educational media that provides a unique experience for learners to enhance their English language skills. The design of this media integrates a website with 360-degree images, ensuring coherence between visual content and learning materials. The selected materials have been aligned with learning outcomes and curricula relevant to the study program. This website is specifically designed for English language learning in higher education, offering an interface accessible across various browsers and devices, both desktop and mobile. Research findings indicate a significant improvement in student learning outcomes, as evidenced by pre-test and post-test scores with average values of 69.95 and 85.33, respectively. These findings suggest the effectiveness of VR media in enhancing students’ English language proficiency.